HEALTHY LIMBS – BASIS OF HIGH PRODUCTIVITY OF SWINE - Семіренко, В. В. (Scientific Progress & Innovations, 2014)
The article deals with a importance of the functional state of limbs in swine. It is spoken in detail about the diagnostic study of hoofs and the impact of risk factors of lameness. It should be noted that infringement of function of musculoskeletal system of swine substantially affects their productivity. The article gives valuable information about the diagnostic features of hoofs in swine. The main idea of authors is to conduct correct diagnosis and prevention of disease of functional state of limbs and hoofs. The article is of great help to doctors of veterinary medicine, researchers in further investigations in swine breeding.